COCHLEAR IMPLANTATION IN A CHILD WITH COMPLEX BILATERAL INNER EAR AND COCHLEO-VESTIBULAR NERVE MALFORMATIONS - Sebastian Cozma; Oana Manolache; Raluca Olariu; Cristian Mârțu; Luminița Rădulescu (Romanian Society of Oral Rehabilitation, 2015)
Introduction: The cochlear implantation in patients with inner ear malformation has always been a challenge even to the most experienced clinicians. We present the case of a child of 8 years old with profound bilateral sensorineural hearing loss and the absence of language development with indication of cochlear implantation as single solution for hearing and speech rehabilitation. Methods: The audiological assessment indicates the cochlear implantation. Preoperative CT scan revealed a bilateral inner ear malformation (cochlear common cavity deformity on the right side, cochlear aplasia on the left ear and bilateral vestibular malformation). Brain magnetic resonance showed the presence of auditory nerve only to the right side. The girl was implanted on the right ear in the common cavity with an Advanced Bionics device, HiRes90K with HiFocus1j electrode. Results: The insertion of the portelectrode inside the malformed inner ear was confirmed by X-ray. Audiological evaluation had shown an average of hearing thresholds at 36,25 dB HL in free field pure tone audiometry at 22 months post-implantation. The speech perception was evaluated according to CAP (categories of auditory performance) index at 5 and to the speech intelligibility rating scale (SIR) to 3. Conclusions: The children with inner ear malformations can safely benefit of cochlear implantation. The results for tonal hearing were close to that of cochlear implanted children with normal ear anatomy, but were limited for speech understanding and speech production.